Antibacterial effect of white tea and black tea extracts on Streptococcus mutans and Streptococcus sobrinus - Abd. Mutalib, Nurul Akmal; Ab.Rahmant, Siti Fatihah; Kusumawardani, Anisa; lchwan, Solachuddin Jauhari Arief (2015)
Objectives: To see the antibacterial activity of white tea and black tea extracts against Sfrepfococcus mutans and Sfrepfococcus sobrinus. Materials and methods: Ethanol-based and water-based extracts of white tea and black tea were used in this study. Ten grams of each extract was dissolved in 1Oml distilled water and ethanol (99.9%). Agar cultures of Streptococcus mutans and Sfrepfococcus sobrinus were prepared for assessment of inhibition zone. Disc diffusion method was performed in triplicate and the zones of inhibition were measured after 72 hours of incubation period. Ampicillin was used as a positive control while ethanol and distilled water as the negative control. Results: The ethanol-based and water-based white tea extracts showed antibacterial activity against Streptococcus mutans (mean; I : 0.98t0.1Omm and 0.98t0.03mm) and Sfreptococcus sobrinus (I :1.07x0.11mm and 0.75t0.05mm), while ethanol-based and water-based extracts of black tea showed antibacterial effect against Sfrepfoco ccus mutans only (.I :0.97t0.85mm and 1.58t0.38mm). However, the inhibition zone of ethanol-based and water-based extracts of black tea against Streptococcus mufans were greater compared to white tea. The greatest inhibition zone was shown by ampicillin which was the positive control (I :413t0.25mm and 2.70t0.61mm). Gonclusions: lt is suggested that ethanol-based and water-based white tea and black extracts possess an antibacterial activity. Further study should be done to prove the beneficial of black and white tea extract as a mouth wash against dentalcaries in oralcavity.